From the Desk of Editor in Chief Vol.30(2) - Ahasan, HAM Nazmul (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11425 J Bangladesh Coll Phys Surg 2012; 30: 121